Bullying or fat shaming? The risk factors of Body Dysmorphic Disorder (BDD) in teenage girls - SUMI LESTARI (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aims to examine the extent to which fat shaming contributes to the development of Body Dysmorphic Disorder (BDD) in adolescent girls.Method: Teenage girls with BDD were surveyed using a qualitative, case-study approach, with initial screening involving the use of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) to establish a diagnosis of BDD. The data in this study were also analyzed using a holistic Yin perspective.Findings: The data from this study shows that everyone who participated in the survey endured some form of negative bullying because of their weight, most notably from members of their own family and friends (schoolmates and playmates). Confidence, pride, self-acceptance, self-conception, social interaction, eating disorders, camouflage, and BDD are all negatively impacted for those respondents who are subjected to fat-shaming regularly.Implications/Novel Contribution: The study results imply that people should be taught to value themselves and others regardless of their size, shape, or appearance. Additionally, one should stop trying to improve themselves or others by measuring themselves against artificial benchmarks or other people.